2009
DOI: 10.1016/j.tetlet.2009.06.132
|View full text |Cite
|
Sign up to set email alerts
|

Selenonium ionic liquid as efficient catalyst for the Baylis–Hillman reaction

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…An early application of Lewis‐acidic selenium salts was published in 2009 by Lenardão and colleagues. The addition of phenyl butyl ethyl selenonium tetrafluoroborate (PhBuEtSe + BF 4 – ) resulted in a significant acceleration of the Morita–Baylis–Hillman reaction of aldehydes and electron‐deficient alkenes . Ke, Yeung, and colleagues relied on similar selenonium cations in 2017 to catalyze the electrophilic bromination of arenes and aldol‐type reactions .…”
Section: Chalcogen Bondingmentioning
confidence: 99%
“…An early application of Lewis‐acidic selenium salts was published in 2009 by Lenardão and colleagues. The addition of phenyl butyl ethyl selenonium tetrafluoroborate (PhBuEtSe + BF 4 – ) resulted in a significant acceleration of the Morita–Baylis–Hillman reaction of aldehydes and electron‐deficient alkenes . Ke, Yeung, and colleagues relied on similar selenonium cations in 2017 to catalyze the electrophilic bromination of arenes and aldol‐type reactions .…”
Section: Chalcogen Bondingmentioning
confidence: 99%
“…To further explore this area and take benefit of the tellurium enhanced ChB property, we are currently designing tellurium‐based catalysts. Inspired by the works of Lenardão [18] and Yeung [19] who demonstrated that selenonium could act as organic Lewis acid and promote reaction, we designed new telluronium salts and studied them, and we report here their ChB ability and for the first time the high efficiency of these telluronium species as organocatalysts in typical reactions (Scheme 1, bottom).…”
Section: Methodsmentioning
confidence: 99%
“…In 2001, Afonso, Santos, and coworkers, and later Ko's group, reported that imidazolium‐based IL such as [BMIM][PF 6 ] appeared to accelerate significantly the rates of the Baylis–Hillman reaction. Since then, a number of different ILs supporting the Baylis–Hillman reaction has been reported, being most of them imidazolium‐based ILs . However, Aggarwal and co‐workers found that [BMIM][PF 6 ] in the presence of bases such as DABCO can also yield a side product by reaction of the deprotonated imidazolium salt at its C‐2 position with the aldehyde (Scheme B) .…”
Section: Introductionmentioning
confidence: 99%